AN ANALYSIS OF STUDENTS’ ENGLISH-SPEAKING COMPREHENSIBILITY - Syamsuri, Atifa Dila; Noni, Nurdin; Munir, Munir (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This research aims to find out the level of students' English-speaking comprehensibility in MAN 2 Kota Makassar. The research is conducted using a speaking test to collect data. The data in the research are data from speaking tests using English regarding students' speaking comprehensibility, obtained by giving a list of themed questions to students in the bilingual class (XI 4) as a form of data retrieval and direct documentation, and then the researcher analyzes it. The researcher used descriptive quantitative analysis to find the patterns of samples' answers regarding factors that affect students and certain themes to decide their speaking comprehensibility level. The results of this research are expected to have implications for the teaching and learning process, especially in English language learning. Besides that, this research is expected to improve teachers’ critical thinking and strategy for teaching speaking skills in English lessons. The teacher can use this information to make a new lesson plan or teaching strategy for teaching English because it is the perfect reference for all researchers that interested in writing English in the near future.